Chronic wounds in a multiethnic Asian population: a cost of illness study - Nicholas Graves; Kelvin Bryan Tan; Jackie Ho; Ganga Ganesan; Yi Zhen Ng; Keith Harding; David Carmody; Orlanda QM Goh; Tze Tec Chong; Priya Bishnoi; Ang Shin Yuh; Zhiwen Lo; et al. (BMJ Open, 2023)
Objective To estimate the ‘cost of illness’ arising from chronic wounds in Singapore.Design Incidence-based cost of illness study using evidence from a range of sources.Setting Singapore health services.Participants We consider 3.49 million Singapore citizens and permanent residents. There are 16 752 new individuals with a chronic wound in 2017, with 598 venous ulcers, 2206 arterial insufficiency ulcers, 6680 diabetic ulcers and 7268 pressure injuries.Primary outcome measures expressed in monetary terms are the value of all hospital bed days lost for the population; monetary value of quality-adjusted life years (QALYs) lost in the population; costs of all outpatient visits; and costs of all poly clinic, use of Community Health Assist Scheme (CHAS) and emergency departments (EDs) visits. Intermediate outcomes that inform the primary outcomes are also estimated.Results Total annual cost of illness was $350 million (range $72–$1779 million). With 168 503 acute bed days taken up annually (range 141 966–196 032) that incurred costs of $139 million (range 117–161 million). Total costs to health services were $184 million (range $120–$1179 million). Total annual costs of lost health outcomes were 2077 QALYs (range −2657 to 29 029) valued at $166 million (range −212 to 2399 million).Conclusions The costs of chronic wounds are large to Singapore. Costs can be reduced by making positive investments for comprehensive wound prevention and treatment programmes.